FIGURATIVE LANGUAGE IN THE ALBUM "AM" BY ARCTIC MONKEYS - Sari, Een Laila; Syaputri, Komala Dwi (Jurnal Ilmiah Bina Bahasa, 2024)
The purpose of this study were to categorize different forms of figurative language and interpret their meaning in the Arctic Monkeys album "AM". This study focused on every song on the Arctic Monkeys album, namely "AM." The study looked at a total of twelve songs. The qualitative descriptive approach was employed in this study since it is thought to be the most effective for summarizing the analysis findings. 6 categories of figurative language are identified by the study findings in the album "AM." For a total of 38 data points, there are 6 metaphors, 7 similes, 9 personifications, 5 metonymy, 3 synecdoche, and 8 hyperbole. It was discovered that this kind of personification and hyperbole was frequently utilized in the song lyrics on this album. The results of this study support the notion that figurative language was crucial for elucidating musical meaning. Together with other material, this research offers readers helpful advice on how to better comprehend figurative language and how its use might affect the meaning of songs.